Сравнительные исследования двухканального щелевого теплообменника и существующего на рынке аналога - Malkin, E. C.; Nikolaenko, Yu. E.; Furtat, I. E.; Danilov, A. M.; Nikolaenko, T. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The thermal characteristics of a newly developed two‑channel slot water‑cooled aluminum heat exchanger for a high‑power electronic component and a commercially available copper water‑cooled heat exchanger (Titan) have been experimentally investigated in both closed and open water‑cooling systems. Graphical dependencies of the dissipated power on the average temperature of the heat‑flow simulator are presented. It is shown that the slot heat exchanger provides higher values of dissipated power at the same simulator temperature. At a simulator temperature of +60 °C for the heat‑generating component, the dissipated power in the closed cooling system increased from 112 to 172 W, and in the open system from 234 to 307.4 W.